Reducing suffering in animal models and procedures involving seizures, convulsions and epilepsy - Wolfensohn, S; Hawkins, P; Lilley, E; Anthony, D; Chambers, C; Lane, S; Lawton, M; Robinson, S; Voipio, H; Woodhall, G (2013)
This report is based on discussions and submissions from an expert working group consisting of veterinarians, animal care staff and scientists with expert knowledge relevant to the field and aims to facilitate the implementation of the Three Rs (replacement, reduction and refinement) in the use of animal models or procedures involving seizures, convulsions and epilepsy. Each of these conditions will be considered, the specific welfare issues discussed, and practical measures to reduce animal use and suffering suggested. The emphasis is on refinement since this has the greatest potential for immediate implementation, and some general issues for refinement are summarised to help achieve this, with more detail provided on a range of specific refinements. © 2012 Elsevier Inc.